A Warrior's Spirit: Warriors Novellas # 16-18 - Hunter, Erin; Richardson, Owen; Stevenson, Dave (New York, NY : HarperCollins, 2020)
"In three novellas from the world of the warrior cat Clans, SkyClan warrior Pebbleshine is separated from her Clan, a young rogue is forced to strike out on his own, and Mothwing finds a unique path and relationship to StarClan as WindClan's medicine cat"--.
Pebbleshine's kits -- Tree's roots -- Mothwing's secret.
Ages 8-12.
Grades 4-6.
Keywords: Children's stories, American; Cats -- Juvenile fiction; Cats -- Fiction; Fantasy; Fantasy; Novellas